Synthesis of γ,δ-Unsaturated Selenoamides via the Seleno-Claisen Rearrangement of in situ Generated Allylic Vinyl Selenides from Selenoamides and Allylic Bromides - Murai, Toshiaki; Ezaka, Tatsuya; Kato, Shinzi (Synthesis, 2012)
The deprotonation of α-monosubstituted selenoamides with LDA followed by allylation gives γ,δ-unsaturated selenoamides in good to high yields. In the initial step, allylation may take place at the selenium atom of lithium eneselenolates to form allylic vinyl selenides, which then undergo seleno-Claisen rearrangement. As allylic bromides, γ,γ-disubstituted compounds such as geranyl and neryl bromides could also be used to give products that incorporated tertiary-quaternary stereogenicity with high efficiency.
Keywords: seleno-Claisen rearrangement; γ,δ-unsaturated selenoamides; tertiary-quaternary stereogenicity; high stereoselectivity